Evaluation of bifunctional applications of CuFe2O4 nanoparticles synthesized by a sonochemical method. (January 2021) - Amulya, M.A. Shilpa; Nagaswarupa, H.P.; Kumar, M.R. Anil; Ravikumar, C.R.; Kusuma, K.B.; Prashantha, S.C.
Abstract: Morphological, electrochemical, and dye photodegradation studies on CuFe2 O4 nanoparticles (NPs) prepared by a probe sonication method are presented. Powder X-ray diffraction (PXRD) analysis indicated an average crystal size of 35–40 nm for the synthesized NPs. Diffuse-reflectance spectroscopy (DRS) and measurement of the band-gap energy indicated semiconductor behaviour. Vibrating sample magnetometry (VSM) studies at 300 K clearly revealed that CuFe2 O4 NPs exhibit weak ferromagnetic behaviour. Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) have been applied to analyze the electrochemical properties of the NPs. A CuFe2 O4 NP electrode showed a greater response in an acidic medium (0.1 m HCl) than in a basic medium (0.1 m NaOH). Specific capacitance values of 1.54 and 0.02 F g −1 were calculated from cyclic voltammograms at the CuFe2 O4 electrode vs. an Ag/AgCl electrode in 0.1 m HCl and 0.1 m NaOH, respectively, at a scan rate of 10 mV/s. The electrode also showed high sensitivity for paracetamol, good cycling stability, and high rate capability. From EIS data, the CuFe2 O4 NPs showed pseudocapacitive characteristics. CuFe2 O4 NPs have been employed as a photocatalyst for the removal of Methylene blue (MB) and Drimarene yellow (DY) dyes, whereby pH proved to be crucial. Under UV light, the degree of photocatalytic degradation was found to be high for MB (94%) but low for DY (29%). Highlights: CuFe2 O4 nanoparticles have been synthesized by a sonochemical method. The electrochemical properties of CuFe2 O4 nanoparticles have been examined by CV and EIS. The obtained CuFe2 O4 is a candidate material for sensor and supercapacitor applications. A CuFe2 O4 electrode shows pseudocapacitive properties.